2020
DOI: 10.3390/ma13204692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Drying Method of Pine and Beech Wood on Fracture Toughness and Shear Yield Stress

Abstract: The modern wood converting processes consists of several stages and material drying belongs to the most influencing future performances of products. The procedure of drying wood is usually realized between subsequent sawing operations, affecting significantly cutting conditions and general properties of material. An alternative methodology for determination of mechanical properties (fracture toughness and shear yield stress) based on cutting process analysis is presented here. Two wood species (pine and beech)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…Their results show that the fracture properties of the modified materials depend not only on density, but also on the type of modification, cell wall degradation, and the internal structure. In the work of [ 79 ], the authors focus on the various drying techniques and their influence on the fracture parameters. On the basis of their research, they conclude that an increase in the wood drying temperature and, thus, its thermal modification, lead to higher fragmentation and graininess of the resulting sawdust during machining.…”
Section: Resultsmentioning
confidence: 99%
“…Their results show that the fracture properties of the modified materials depend not only on density, but also on the type of modification, cell wall degradation, and the internal structure. In the work of [ 79 ], the authors focus on the various drying techniques and their influence on the fracture parameters. On the basis of their research, they conclude that an increase in the wood drying temperature and, thus, its thermal modification, lead to higher fragmentation and graininess of the resulting sawdust during machining.…”
Section: Resultsmentioning
confidence: 99%
“…Beltrami first found that critical energy depends on the uniaxial yield or torsion . This approach also opened up the possibility of using many other forms of experimental data such as: Vigers hardness, Sharpy energy, toughness critical energy, cleavage energy, and so on (see Orłowski et al [ 22 , 23 ]).…”
Section: The Materials Effort Description By the Energy Approachmentioning
confidence: 99%
“…Razavi and Berto [ 52 ] proposed a new fixture for fracture testing under mixed-mode I/II/III loading. Chuchala et al [ 53 ] determined the critical-stress-intensity factor and shear yield stress for pine and beech woods based on the cutting machine’s power signal. In addition, they investigated four different drying methods and showed that the drying method has a meaningful effect on the critical-stress-intensity factor and shear yield stress.…”
Section: Introductionmentioning
confidence: 99%